Co-expression of CD79a (JCB117) and CD3 by lymphoblastic lymphoma. - Pilozzi, E; Pulford, K; Jones, M; Müller-Hermelink, H; Falini, B; Ralfkiaer, E; Pileri, S; Pezzella, F; De Wolf-Peeters, C; Arber, D; Stein, H; Mason, D; et al. (1998)
Acute lymphoblastic leukaemia/lymphoma is a malignant disorder derived from the clonal proliferation of lymphoid precursor cells. Whether the tumour cells are of B- or T-cell type is an important criterion for prognosis which has not been available previously to pathologists, due to the lack of a reliable early B-cell marker functioning on routinely processed material. This has changed with the production of monoclonal antibodies against the B-cell signalling molecule CD79a. CD79a is expressed on normal and neoplastic B cells from the early stages of B-cell maturation and has been considered to be B-cell-specific. Currently available antibodies against CD79a, in particular JCB117, allow the identification of B cells, and hence B lymphoblastic disease, in paraffin-embedded material. In this study, the expression of CD79a (JCB117) and CD3 has been investigated in 149 cases of T and 68 cases of B lymphoblastic leukaemia/lymphoma. For the first time, co-expression of CD79a (JCB117) and CD3 is reported in 10 per cent of cases of T lymphoblastic leukaemia/lymphoma. This finding raises questions about the co-expression of T- and B-cell markers in the development of lymphocytes, benign as well as malignant, and alerts pathologists to a potential problem in diagnosis.